PENGARUH PENERAPAN MODEL PEMBELAJARAN BAMBOO DANCING BERBANTUAN PERMAINAN ULAR TANGGA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Dian Lestari; Mumun Munawaroh; Hendri Handoko (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2019)
In learning at school, mathematics subjects are considered a difficult subject. This assumption willaffect the students' mathematics learning outcomes. The teaching and learning process still uses theold paradigm, which is dominated by the role of teacher activities and still uses the lecture method, sothat the method does not attract the attention of students. Therefore, a learning model is needed toovercome this problem. One of the student-centered learning models is the bamboo dancing learningmodel. In addition to the selection of learning models, fun teaching methods need to be supported bythe presence of learning media that attract students' attention. One of them is the media game stairs.This study aims to determine the influence, response of students, and increase the character ofresponsibility in bamboo dancing learning assisted by snake and ladder games in improving studentmathematics learning outcomes. This learning model was tested on students in Cirebon City MTs AlHidayah GUPPI using experimental classes, namely class VII as many as 20 students with the designof one group Pre-Test-Post-Test design. Data collection techniques in this study through tests,questionnaires and observations. Descriptive quantitative data analysis with the results (1) Themagnitude of the influence of the application of bamboo dancing learning models assisted by snakesand ladders in improving mathematics learning outcomes by 53.6%. (2) Students 'response to theinfluence of the application of bamboo dancing learning models assisted by snake and ladder games toimprove students' mathematics learning outcomes in the strong category with a percentage of 76.2%.(3) The sense of responsibility of students in the application of bamboo dancing learning modelsassisted by snake and ladder games from the first meeting to the sixth meeting has increased, the finalresults obtained from the average character values of individual responsibility are 3.63, and theaverage value social responsibility character of 3.7. In the calculation of the t-test the average pretestvalue is 26.95 and the posttest value is 94.1. This shows that the application of bamboo dancingmodels assisted by snakes and ladders can improve students' mathematics learning outcomes.Keywords: Bamboo Dancing, Snake Ladder Game, Character, Mathematics Learning Outcomes.